2021
DOI: 10.1002/aet2.10619
|View full text |Cite
|
Sign up to set email alerts
|

Affective, cognitive, and behavioral outcomes from a resident personal finance curriculum pilot project

Abstract: Background:The transition to residency marks a significant shift in the financial circumstances of medical trainees. Despite existing resources, residents still cite uncertainty in this domain. A personal finance curriculum is needed to close this educational gap and improve the financial well-being of trainees. Methods:The curriculum was developed using Kern's framework. Two needs assessments informed the consensus development of goals and objectives, educational strategies, and assessments. Course material w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“… 32 Finally, two studies showed an increased utilisation of knowledge (Behaviour). 13 30 33 38 However, no study revealed the impact of the curricula on participant organisations, employers or households (Results).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 32 Finally, two studies showed an increased utilisation of knowledge (Behaviour). 13 30 33 38 However, no study revealed the impact of the curricula on participant organisations, employers or households (Results).…”
Section: Resultsmentioning
confidence: 99%
“…If there are time constraints, the topics labelled as optional may be dropped. Of note, the curricula may be delivered in-person or virtually as recommended by Shappell et al , 8 and as executed by Shappell et al 13 and Grewal and Sweeney. 10 Virtual content can be delivered either synchronously or asynchronously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations